Konstruksi Sosial dalam Tradisi Pembacaan Surah Yasin: Studi Living Qur’an di Kampung Rawa Saban Pakuhaji Tangerang Banten - Maimunah, Siti (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2024)
This study aims to determine the process of social construction of the recitation of surah Yasin on Eid al-Fitr as a form of social response of the community to the Qur'an. In this case, Kampung Rawa carries out this tradition at the time after Eid al-Fitr prayers.   This research uses field research (Field Research). The theory used to answer the problem formulation uses Peter L. Berger's theory of social construction. The focus of the study in this study discusses how the social construction process of reading surah Yasin on Eid al-Fitr. This research found that the tradition of recitation of surah Yasin is one of the phenomena of the application of the Living Qur'an by the community